Comparative genomics studies of Rpp1 gene associated with soybean (Glycine max L.) rust resistance: Comparative genomics studies of Rpp1 gene associated with soybean (Glycine max L.) rust resistance - MILIND RATNAPARKHE; SHIVAKUMAR M; NATARAJ V; VIRAJ KAMBLE; SANJAY GUPTA (Journal of Oilseeds Research, 2020)
Whole genome sequence of rust resistant and susceptible lines were used for comparative genomics studies.Three putative NBS-LRR genes were identified at Rpp1 locus associated with soybean rust.